Curriculum XXI : lo esencial de la educación para un mundo en cambio - Jacobs, Heidi Hayes; Manzano Bernardéz, Pablo (Educación hoy (Narcea (Firm)). Estudios., 2014)
Contains articles that discuss ideas to improve and update the K-12 curriculum to prepare students for life in the twenty-first century, covering content and assessments, program structures, technology and media literacy, globalization, sustainability, and the thinking habits of students, teachers, and administrators.